Optimization of condensate fractionation unit using response surface methodology - Ibrahim, M.T. (Trans Tech Publications Ltd, 2014)
Response Surface Method involving central composite design is employed to determine the optimal configuration of nine factors for maximizing the profit of a Condensate Fractionation Unit. When compared with the results from the base case and Taguchi method, the result from RSM shows higher profits by 33.1 and 1.16, respectively. A further benefit of 0.64 is noticed when three insignificant factors were removed from the nine-factor experiment due to interactions between factors. Â© 2014 Trans Tech Publications, Switzerland.